Molecular cloning and characterization of a novel human variant of RIC-3, a putative chaperone of nicotinic acetylcholine receptors. Issue 6 (7th October 2008) - Seredenina, Tamara; Ferraro, Teresa; Terstappen, Georg C.; Caricasole, Andrea; Roncarati, Renza
Abstract : Recent reports demonstrate that the RIC-3 (resistant to inhibitors of cholinesterase-3) protein is important for the maturation of nAChRs (nicotinic acetylcholine receptors). In the present study RIC-3e, a novel variant of RIC-3, is described. This variant contains a deletion of exons 4 and 5 of RIC - 3, resulting in a protein product lacking a conserved coiled-coil domain. Like RIC-3, the new variant is predominantly, but not exclusively, expressed in the brain. The analysis of expression of variant RIC - 3 mRNA and of α 7 - nAChR mRNA in a set of human tissues shows a similar profile. The RIC-3e protein is functionally active and enables surface expression of mature α7-nAChRs in cell lines not otherwise permissive for the expression of this receptor.